2015
DOI: 10.1165/rcmb.2014-0322oc
|View full text |Cite
|
Sign up to set email alerts
|

Resistin-Like Molecule α in Allergen-Induced Pulmonary Vascular Remodeling

Abstract: Resistin-like molecule a (RELMa) has mitogenic, angiogenic, vasoconstrictive, and chemokine-like properties and is highly relevant in lung pathology. Here, we used RELMa knockout (Retnla 2/2 ) mice to investigate the role of RELMa in pulmonary vascular remodeling after intermittent ovalbumin (OVA) challenge. We compared salineand OVA-exposed wild-type (WT) mice and found that OVA induced significant increases in right ventricular systolic pressure, cardiac hypertrophy, pulmonary vascular remodeling of intra-al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 41 publications
2
18
0
1
Order By: Relevance
“…In another study of repeated intratracheal instillations of S. chartarum, goblet cell metaplasia was observed after seven exposures, but not after a single exposure, indicative of airway remodeling after S. chartarum exposure (25). In agreement with Fan and colleagues, retnla was increased with arterial remodeling, together with asthma pathogenesis and tissue remodeling-associated proteins (32). These proteins and respective genes were significantly increased after both viable S. chartarum exposures compared with air-only and HIC controls, as well as at an earlier time point in strain A-exposed versus strain B-exposed mice.…”
Section: Discussionsupporting
confidence: 75%
“…In another study of repeated intratracheal instillations of S. chartarum, goblet cell metaplasia was observed after seven exposures, but not after a single exposure, indicative of airway remodeling after S. chartarum exposure (25). In agreement with Fan and colleagues, retnla was increased with arterial remodeling, together with asthma pathogenesis and tissue remodeling-associated proteins (32). These proteins and respective genes were significantly increased after both viable S. chartarum exposures compared with air-only and HIC controls, as well as at an earlier time point in strain A-exposed versus strain B-exposed mice.…”
Section: Discussionsupporting
confidence: 75%
“…4 Furthermore, we have shown that IL-17 expression in the lung is significantly suppressed in global HIMF/RELMα knockout mice as compared with that in wild-type mice during allergic inflammation. 47 It is reasonable to speculate that an increase in IL-6 in lung resident cells in response to HIMF can induce a sequential Th2/Th17 response. In accordance with our results, a recent study by Jang et al 48 showed that hRETN preferentially binds myeloid cells such as monocytes and macrophages in the lung during parasitic infections, and promotes proinflammatory cytokine expression.…”
Section: Discussionmentioning
confidence: 99%
“…Resistin-like molecule (RELM)-α, a striking downstream product of the IL-4 and IL-13 signaling pathways in allergen-and parasite-associated Th2 responses, is overexpressed in the lungs regulated by Th2-and IL-13-mediated inflammation and hypoxia. RELM-α-knockout mice inhibited pulmonary vascular remodeling and the increase of pulmonary pressure and cardiac hypertrophy, thus leading to less vessel muscularization, less perivascular inflammation and reduced medial thickness of intraalveolar vessels [53]. It was observed that the expressions of RELM-α, were increased associated with an enhanced IL-13 signaling in infected wild-type and IL-13Rα2 −/− but not IL-13Rα1 −/− mice.…”
Section: Treatmentmentioning
confidence: 97%